A contrastive analysis of semantic features of the verb “cut” in English collocations and their equivalents in Vietnamese - Tạ, Thị Kim Oanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
As we know, verbs play an important role in using language. In this paper, the research focuses on the semantic features of the verb “cut” in English collocations and the verb “cắt” in Vietnamese collocations. Then, this study finds out the similarities and differences between these two verbs in terms of semantic features. The descriptive research method is employed to give an in-depth and detailed description of collocations of lexical verb “cut” in English and “cắt” in Vietnamese. The data are collected from different sources such as dictionaries, proverb books, stories, etc…Then, the data are analyzed systematically to generalize the uses of these collocations. These findings lead to the implications for teachers and students in teaching and learning “cut” collocations for translating collocations from English into Vietnamese and vice versa.